Effects of side reactions on the kinetics of nanoporous gold formation revealed by real-time X-ray scattering during electrolytic dealloying. Issue 35 (11th August 2021) - Welborn, Samuel S.; Corsi, John S.; Wang, Lin; Lee, Asaph; Fu, Jintao; Detsi, Eric
Abstract : Simultaneous SAXS/WAXS studies elucidate passive surface film growth during formation of nanoporous gold by electrolytic dealloying in HClO4, but not in HNO3 . This passive surface film hampers dealloying kinetics and slows ligament growth/coarsening. Abstract : Nanoporous gold (NP-Au) is used in various energy applications. However, little attention has been paid to the nature of surface films which can grow via side reactions during the formation of NP-Au by selective leaching. These films could significantly impact both the kinetics of NP-Au formation by selective leaching, and the performance of this NP-Au in specific energy applications. While it has been reported that complete removal of Ag from a Au–Ag parent alloy by selective leaching is kinetically more sluggish in HClO4 than in HNO3, and that the resulting structure size of NP-Au is smaller when formed in HClO4 compared to HNO3, these findings were not attributed to the growth of surface film via side reactions during selective leaching. In this work, small-angle and wide-angle X-ray scattering (SAXS and WAXS) are used in real time during NP-Au formation by selective electrolytic leaching of Ag from a Au–Ag parent alloy in 1 M HClO4 and 1 M HNO3 to demonstrate that the sluggish dealloying behavior in HClO4 results from the growth of a surface film during dealloying. In HClO4, Ag + ions released from the Au–Ag working electrode spontaneously react with Cl − ions released from ClO4 − reduction at the counter electrode to form an insoluble AgCl passive film on NP-Au. The AgCl hinders Ag dissolution and surface diffusion of Au atoms, slowing down the reaction kinetics and the rate of ligament growth. Our findings shed light on dealloying reaction mechanisms and will contribute to better control of the morphology and surface chemical state of nanoporous metals for energy applications.